The Storm Keeper's Island - Doyle, Catherine, 1990- (Bloomsbury Children's Books, 2019)
Fionn Boyle, terrified of the sea, must spend the summer with his older sister, Tara, and their grandfather on Arranmore, an island that has been known to make people disappear, and seems to be restless again.